Effect of Moisture Content on Bursting Liability of Sandstone due to Freeze-Thaw Action - Kesheng Li; Maotong Li; Deng Zhang; Chuanxiao Liu; Depeng Ma (Shock and Vibration)
Moisture content (MC) and freeze-thaw (F-T) process have an important influence on the mechanical properties of rock and its rockburst tendency in the cold region. In addition, uniaxial compressive strength (UCS) of rock is of great importance in evaluating weathering durability, frost resistance, and bursting liability of rock. In this study, the UCS of rock and bursting liability index of rock including elastic energy index (WET), impact energy index (WCF), elastic strain energy index (ES), and modified values of brittleness index (BIM) were measured by laboratory tests. These tests were implemented in six different MC (0, 0.58, 1.06, 1.82, 2.43, and 2.80%) and 20 F-T cycles. The relationship between rock mechanical properties, bursting liability of rock, and MC after freeze-thaw damage was established, and the control mechanism of moisture content on mechanical properties and rockburst tendency of rocks in cold regions was revealed. Uniaxial compressive test results showed that the UCS of rock decreases significantly with the increase of MC. Under the action of F-T cycles, WET, WCF, and ES decrease with the increase of MC, and BIM of rock increases gradually. This indicates that the rockburst tendency of sandstone decreases with the increase of MC. To calculate WET, WCF, ES, and BIM of sandstone samples, new empirical equations were established and put forward under different MC after 20 F-T cycles.